Developing an air-conditioner switching control using fuzzy logic / Mohamad Suhaime Mohd Sharif - Mohd Sharif, Mohamad Suhaime (1997)
This thesis introduces a fuzzy system in an expert system control. For a system control , a fuzzy logic is used to control the switching of an air-conditioner to cool the room temperature . The switching are design to a types of fixed value. This involved the fuzzy tech tool software and a process of simulation using the Borland C++. An object-oriented programming techniques will be involves in the development of the fuzzy control. Object-oriented programming allows the simulation to be built in a modular fashion making it both expandable and easy maintainable. The simulation will responds to the given data input which is set in MS-DOS operating system . The crisp output data is shown on the monitor.